A lithium ion battery separator, a preparation method thereof and a lithium ion battery
Patent Information
- Application Number
- CN202511577000.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-10-31
AI Technical Summary
[0006]本发明提供一种锂离子电池隔膜及其制备方法和锂离子电池,用以解决现有技术中隔膜难以兼具优异耐热性、高机械强度、高抗穿刺性能的缺陷
[0026]优选地,所述干燥的温度为80~100℃,时间为4~8h。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a lithium-ion battery separator, its preparation method, and a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and environmental friendliness. As a key internal component of lithium-ion batteries, the battery separator functions to separate the positive and negative electrodes, prevent short circuits, and allow lithium ions to move freely, making it crucial for battery safety, cycle performance, and rate performance.
[0003] Currently, most commercially available lithium-ion battery separators are polyolefin-based membranes, such as polyethylene (PE) and polypropylene (PP) separators. Although these separators have good ion conductivity and mechanical flexibility, they suffer from severe thermal shrinkage at high temperatures, which can lead to separator failure, internal short circuits, and even thermal runaway and other safety accidents.
[0004] In addition, there is still room for improvement in the mechanical strength and puncture resistance of polyolefin separators to cope with external stresses such as compression and impact that batteries may encounter during manufacturing and use, thereby further ensuring the long-term stability and safety of batteries.
[0005] Therefore, how to develop a new type of lithium-ion battery separator that combines excellent heat resistance, high mechanical strength, and high puncture resistance to significantly improve the overall safety and durability of lithium-ion batteries is a key issue that urgently needs to be addressed in the current field of battery separator technology. Summary of the Invention
[0006] This invention provides a lithium-ion battery separator, its preparation method, and a lithium-ion battery, to solve the defects in the prior art where separators are difficult to simultaneously possess excellent heat resistance, high mechanical strength, and high puncture resistance.
[0007] This invention fundamentally solves the problem of balancing various properties in existing technologies by precisely controlling the size and ratio of nanofibers and ceramic nanoparticles in the diaphragm.
[0008] Specifically, the present invention provides a lithium-ion battery separator, comprising a base film and a coating attached to at least one surface of the base film, wherein the coating is prepared from raw materials including nanofibers and ceramic nanoparticles; wherein the relationship between the diameter d and length L of the nanofibers and the average particle size D of the ceramic nanoparticles satisfies: D≤(L / d)≤2D, d is 10~50nm, L is 3000~20000nm, and D is 150~400nm.
[0009] The lithium-ion battery separator provided by this invention has a coating on the surface of the base film composed of nanofibers and ceramic nanoparticles of a specific size range. By precisely controlling the aspect ratio (L / d) of the nanofibers and the average particle size (D) of the ceramic nanoparticles, a unique and highly optimized porous microstructure can be constructed. This allows the separator to achieve ultra-thin characteristics while significantly improving its heat resistance, mechanical strength, and resistance to lithium dendrite penetration, and maintaining suitable air permeability to ensure efficient lithium-ion transport. This comprehensively improves the safety, cycle life, and energy density of lithium-ion batteries.
[0010] According to the lithium-ion battery separator of the present invention, the relationship between the mass percentage P% of the ceramic nanoparticles in the coating and the mass percentage K% of the nanofibers in the coating satisfies: 2 < (P / K) 0.7 <25, P is 75~93, K is 1~20. This optimized mass ratio ensures the synergistic effect among the components in the coating. While the high ceramic content provides thermal stability and puncture resistance, the nanofibers can still form an effective network to enhance mechanical flexibility and suppress dendrites, so that the membrane has superior key properties (such as high temperature stability, dendrite resistance, mechanical strength and ion transport).
[0011] Preferably, 3.8 < (P / K) 0.7 <14.6, P is 83~92, K is 2~12.
[0012] According to the lithium-ion battery separator of the present invention, the nanofibers are selected from one or more of aramid fibers, cotton fibers, and bacterial cellulose.
[0013] According to the lithium-ion battery separator of the present invention, the ceramic nanoparticles are selected from one or more of alumina, boehmite, barium titanate, magnesium oxide, silicon oxide, and magnesium hydroxide. These ceramic materials have excellent heat resistance, high hardness, chemical stability, or specific functions (such as dielectric properties), thereby specifically improving the high-temperature dimensional stability, mechanical strength, and puncture resistance of the separator.
[0014] According to the lithium-ion battery separator of the present invention, the base membrane is a polyolefin base membrane, such as polyethylene and polypropylene, or a composite membrane thereof.
[0015] Preferably, the thickness of the base film is 5~25μm; the porosity of the base film is 55~70%. Controlling the thickness of the base film enables the ultra-thin design required for high energy density in batteries, while controlling the porosity ensures efficient ion conduction channels, providing excellent basic support for the coating, and together constructing a high-performance separator.
[0016] According to the lithium-ion battery separator of the present invention, the thickness of the coating is 0.1~4μm, preferably 0.5~2μm.
[0017] In some specific embodiments, the coating includes a first coating and a second coating respectively disposed on both sides of the base film, and the thickness of the first coating and the second coating are equal.
[0018] The lithium-ion battery separator according to the present invention includes a binder in the raw materials comprising nanofibers and ceramic nanoparticles. The binder effectively enhances the bonding force between the nanofibers and ceramic nanoparticles within the coating, preventing the coating from powdering or peeling off. The binder comprises 2-5% by mass in the coating.
[0019] Preferably, the adhesive is a water-soluble modified polyacrylamide copolymer, specifically a copolymer composed of acrylamide monomers, acrylic monomers, and water-soluble acrylate monomers; wherein the weight ratio of the acrylamide monomers, acrylic monomers, and water-soluble acrylate monomers is 50~80:10~30:10-20.
[0020] The acrylamide monomer is one or more of acrylamide, methacrylamide, N,N-dimethylacrylamide, N-hydroxymethylacrylamide, N,N-methylenebisacrylamide, N-(2-hydroxyethyl)acrylamide, and N-(2-hydroxypropyl)acrylamide.
[0021] The acrylic monomer is one or more of acrylic acid, methacrylic acid, itaconic acid, and aconitic acid.
[0022] The water-soluble acrylate monomers are one or more of the following: 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, and 3-hydroxypropyl methacrylate.
[0023] The lithium-ion battery separator according to the present invention includes a dispersant in the raw materials comprising nanofibers and ceramic nanoparticles. The dispersant effectively prevents the agglomeration of nanomaterials during slurry preparation, ensuring uniform dispersion of nanofibers and ceramic nanoparticles in the coating slurry. The dispersant has a mass percentage content of 1-3% in the coating; preferably, the dispersant is selected from sodium polyacrylate or ammonium polyacrylate.
[0024] Preferably, the molecular weight of the dispersant is 3000-10000.
[0025] The present invention also provides a method for preparing the above-mentioned lithium-ion battery separator, comprising: mixing nanofibers, ceramic nanoparticles, binder, dispersant and solvent to obtain a slurry; coating the slurry onto the base film and drying it; Preferably, the solvent is selected from water. The amount of solvent used is 30-60% of the total mass of nanofibers, ceramic nanoparticles, binders, and dispersants.
[0026] Preferably, the drying temperature is 80~100℃ and the time is 4~8h.
[0027] The present invention also provides a lithium-ion battery, comprising the lithium-ion battery separator described above or a lithium-ion battery separator prepared by the above preparation method.
[0028] This invention precisely controls the size and ratio of nanofibers and ceramic nanoparticles to construct an ultrathin functional coating on the surface of a base film. This coating endows the lithium-ion battery separator with excellent high-temperature dimensional stability (significantly reducing thermal shrinkage), high resistance to dendrite penetration, and enhanced mechanical strength, thereby effectively ensuring battery safety. Simultaneously, it maintains suitable permeability to ensure efficient ion transport and possesses ultrathin characteristics to improve battery energy density. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0030] The nanofibers, ceramic nanoparticles, binders, and dispersants used in the following examples and comparative examples are all commercially available.
[0031] Example 1 This embodiment provides a lithium-ion battery separator, which is composed of a first coating, a base film and a second coating disposed in contact, wherein the overall thickness of the lithium-ion battery separator is 26μm.
[0032] The base film is a polyethylene base film with a thickness of 25μm and a porosity of 65%. The polyethylene base film was purchased from Xingyuan Material, model SD425202.
[0033] The thickness of both the first and second coatings is 0.5 μm. Both coatings consist of nanofibers, ceramic nanoparticles, a binder, and a dispersant. The nanofibers have an average length L of 3000 nm and a diameter d of 10 nm; the nanofibers are aramid fibers. The ceramic nanoparticles have an average particle size D of 150 nm; the ceramic nanoparticles are alumina. The binder consists of N,N-methylenebisacrylamide, methacrylic acid, and 2-hydroxyethyl acrylate in a mass ratio of 50:30:20. The dispersant is ammonium polyacrylate (molecular weight 10000).
[0034] This embodiment further provides a method for preparing a lithium-ion battery separator, specifically including the following steps: Nanofibers (2% by mass), ceramic nanoparticles (92% by mass), binder (3% by mass), dispersant (3% by mass), and deionized water accounting for 40% of the total mass of the above components (nanofibers, ceramic nanoparticles, binder, and dispersant) were mixed and homogenized at high speed to obtain a slurry. The obtained slurry was directly coated onto the upper and lower surfaces of the base film and then dried at 80°C for 8 hours.
[0035] Example 2 This embodiment provides a lithium-ion battery separator, which is composed of a first coating, a base film and a second coating disposed in contact, wherein the overall thickness of the lithium-ion battery separator is 22μm.
[0036] The base film is a polyethylene base film with a thickness of 20μm and a porosity of 68%. The polyethylene base film was purchased from Xingyuan Material, model SD420202.
[0037] The thickness of both the first and second coatings is 1 μm. Both coatings consist of nanofibers, ceramic nanoparticles, a binder, and a dispersant. The nanofibers have an average length L of 20,000 nm and a diameter d of 50 nm; the nanofibers are cotton fibers. The ceramic nanoparticles have an average particle size D of 400 nm; the ceramic nanoparticles are magnesium oxide. The binder consists of acrylamide, acrylic acid, and 2-hydroxyethyl acrylate in a mass ratio of 80:10:10. The dispersant is sodium polyacrylate (molecular weight 10,000).
[0038] This embodiment further provides a method for preparing a lithium-ion battery separator, specifically including the following steps: Nanofibers (12% by mass), ceramic nanoparticles (83% by mass), binder (2% by mass), dispersant (3% by mass) and deionized water accounting for 40% of the total mass of the above components are mixed and stirred at high speed to obtain a slurry. The obtained slurry is directly coated onto the upper and lower surfaces of the base film and then dried at 100°C for 4 hours.
[0039] Example 3 This embodiment provides a lithium-ion battery separator, which is composed of a first coating, a base film and a second coating disposed in contact, wherein the overall thickness of the lithium-ion battery separator is 19μm.
[0040] The base film is a polypropylene base film with a thickness of 15μm and a porosity of 62%. The polypropylene base film was purchased from Xingyuan Material, model SD415202.
[0041] The thickness of both the first and second coatings is 2 μm. Both coatings consist of nanofibers, ceramic nanoparticles, a binder, and a dispersant. The nanofibers have an average length L of 5000 nm and a diameter d of 20 nm; the nanofibers are aramid fibers. The ceramic nanoparticles have an average particle size D of 160 nm; the ceramic nanoparticles are barium titanate. The binder consists of N-(2-hydroxypropyl)acrylamide, itaconic acid, and 2-hydroxypropyl acrylate in a mass ratio of 70 / 20 / 10. The dispersant is sodium polyacrylate (molecular weight 10000).
[0042] This embodiment further provides a preparation method, which specifically includes the following steps: Nanofibers (4% by mass), ceramic nanoparticles (90% by mass), binder (5% by mass), dispersant (1% by mass), and deionized water accounting for 40% of the total mass of the above components are mixed and homogenized at high speed to obtain a slurry. The obtained slurry is directly coated onto the upper and lower surfaces of the base film and then dried at 90°C for 5 hours.
[0043] Example 4 This embodiment provides a lithium-ion battery separator, which is composed of a first coating, a base film and a second coating disposed in contact, wherein the overall thickness of the lithium-ion battery separator is 11.5 μm.
[0044] The base film is a polyethylene base film with a thickness of 10μm and a porosity of 55%. The polyethylene base film was purchased from Xingyuan Material, model SD410202.
[0045] The thickness of both the first and second coatings is 0.75 μm. Both coatings consist of nanofibers, ceramic nanoparticles, a binder, and a dispersant. The nanofibers have an average length L of 10000 nm and a diameter d of 30 nm; the nanofibers are bacterial cellulose. The ceramic nanoparticles have an average particle size D of 300 nm; the ceramic nanoparticles are boehmite. The binder consists of methacrylamide, aconitine, and 2-hydroxyethyl acrylate in a mass ratio of 60:20:20. The dispersant is ammonium polyacrylate (molecular weight 8000).
[0046] This embodiment further provides a preparation method, which specifically includes the following steps: Nanofibers (8% by mass), ceramic nanoparticles (88% by mass), binder (2% by mass), dispersant (2% by mass), and deionized water accounting for 40% of the total mass of the above components are mixed and stirred at high speed to obtain a slurry. The obtained slurry is directly coated onto the upper and lower surfaces of the base film and then dried at 85°C for 6 hours.
[0047] Example 5 This embodiment provides a lithium-ion battery separator, which is composed of a first coating, a base film and a second coating disposed in contact, wherein the overall thickness of the lithium-ion battery separator is 8μm.
[0048] The base film is a polyethylene base film with a thickness of 5μm and a porosity of 56%. The polyethylene base film was purchased from Xingyuan Material, model SD405202.
[0049] The thickness of both the first and second coatings is 1.5 μm. Both coatings consist of nanofibers, ceramic nanoparticles, a binder, and a dispersant. The nanofibers have an average length L of 15000 nm and a diameter d of 40 nm; the nanofibers are cotton fibers. The ceramic nanoparticles have an average particle size D of 200 nm; the ceramic nanoparticles are silicon dioxide. The binder consists of N,N-dimethylacrylamide, acrylic acid, and 3-hydroxypropyl methacrylate in a mass ratio of 55:25:20. The dispersant is ammonium polyacrylate (molecular weight 10000).
[0050] This embodiment further provides a preparation method, which specifically includes the following steps: Nanofibers (10% by mass), ceramic nanoparticles (86% by mass), binder (3% by mass), dispersant (1% by mass), and deionized water accounting for 40% of the total mass of the above components are mixed and homogenized at high speed to obtain a slurry. The obtained slurry is directly coated onto the upper and lower surfaces of the base film and then dried at 95°C for 6 hours.
[0051] Example 6 This embodiment provides a lithium-ion battery separator, which is composed of a first coating, a base film and a second coating disposed in contact, wherein the overall thickness of the lithium-ion battery separator is 12μm.
[0052] The base film is a polyethylene base film with a thickness of 10μm and a porosity of 55%. The polyethylene base film was purchased from Xingyuan Material, model SD410202.
[0053] The thickness of both the first and second coatings is 1 μm. Both coatings consist of nanofibers, ceramic nanoparticles, a binder, and a dispersant. The nanofibers have an average length L of 4000 nm and a diameter d of 20 nm; the nanofibers are aramid fibers. The ceramic nanoparticles have an average particle size D of 180 nm; the ceramic nanoparticles are alumina. The binder consists of acrylamide, methacrylic acid, and 2-hydroxyethyl acrylate in a mass ratio of 65:20:15. The dispersant is sodium polyacrylate (molecular weight 10000).
[0054] This embodiment further provides a preparation method, which specifically includes the following steps: Nanofibers (3% by mass), ceramic nanoparticles (91% by mass), binder (4% by mass), dispersant (2% by mass), and deionized water accounting for 40% of the total mass of the above components are mixed and homogenized at high speed to obtain a slurry. The obtained slurry is directly coated onto the upper and lower surfaces of the base film and then dried at 100°C for 4 hours.
[0055] Example 7 This embodiment provides a lithium-ion battery separator, which differs from Embodiment 2 in that the thickness of the first coating is 0.1 μm and the thickness of the second coating is 0.6 μm.
[0056] Example 8 This embodiment provides a lithium-ion battery separator, which differs from Embodiment 1 only in that the nanofibers in the coating have a mass percentage of 1%, while the rest are changed proportionally according to the original proportions of Embodiment 1.
[0057] Example 9 This embodiment provides a lithium-ion battery separator, which differs from Embodiment 1 only in that the mass percentage of the nanofibers in the coating is 20%, and the rest are changed proportionally according to the original proportions of Embodiment 1.
[0058] Comparative Example 1 This comparative example provides a lithium-ion battery separator, which is a commercially available polyethylene-based film purchased from Shanghai Enjie New Material Technology Co., Ltd., with a thickness of 25μm.
[0059] Comparative Example 2 This comparative example provides a lithium-ion battery separator, which differs from Example 1 only in that the average length L of the nanofibers is 500 nm and the diameter d is 50 nm.
[0060] Comparative Example 3 This comparative example provides a lithium-ion battery separator, which differs from Example 1 only in that the average length L of the nanofibers is 50,000 nm and the diameter d is 40 nm.
[0061] Test Case Performance Testing The present invention tests the performance of the lithium-ion battery separators of the above embodiments and comparative examples. The heat shrinkage rate test method is as follows: the coated separator is cut into A4 size, with the long direction being the MD direction and the short direction being the TD direction. A 100mm×100mm frame is drawn in the middle. 11 A4 sheets of paper are sandwiched on the top and bottom of the separator. After being placed in an oven at 180℃ for 60 minutes, the size of the drawn frame is measured and recorded as L. The heat shrinkage rate is (100-L)%.
[0062] Needle strength, areal density, and air permeability were all tested according to standard methods.
[0063] Needle penetration strength: GB / T 36363-2018 Polyolefin separator for lithium-ion batteries 6.5.3.
[0064] Areal density: the weight of the diaphragm divided by its corresponding area.
[0065] Air permeability: GB / T 36363-2018 Polyolefin separator for lithium-ion batteries 6.5.4.
[0066] The test results are shown in Table 1 below.
[0067] Table 1. Test results of diaphragm performance
[0068] As can be seen from the experimental data in Table 1, the separator prepared by this invention exhibits an extremely low thermal shrinkage rate, meaning its high-temperature safety is significantly improved. Simultaneously, it possesses high mechanical strength (tensile strength and needle penetration strength), effectively resisting physical damage and lithium dendrite penetration. More importantly, these significant performance leaps were achieved while maintaining a lower areal density (i.e., thinner and lighter, which is beneficial for improving battery energy density) without sacrificing necessary permeability (ensuring good ion conduction). In summary, these data strongly demonstrate the breakthrough comprehensive advantages of the separator of this invention in terms of safety, durability, and energy density. Compared to existing separators (Comparative Example 1), the overall performance of the separator of this invention is significantly improved.
[0069] The nanofibers used in Comparative Example 2 had an excessively small aspect ratio, resulting in L / d < D. Consequently, despite the application of a coating, their thermal stability deteriorated sharply, and their mechanical strength was far inferior to that of Example 1. The nanofibers in Comparative Example 3 had an excessively large aspect ratio, resulting in L / d > 2D. This also led to a persistently high thermal shrinkage rate, and their mechanical properties significantly declined compared to Example 1. This result strongly demonstrates that not all coatings can improve performance. Only when the size of the nanofibers can form the synergistic matching structure defined by the present invention with the ceramic particles can an effective support network be constructed, thereby achieving excellent thermal stability and mechanical reinforcement.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium-ion battery separator, comprising a base film and a coating adhered to at least one surface of the base film, characterized in that, The coating is composed of nanofibers, ceramic nanoparticles, a binder, and a dispersant; wherein the diameter d and length L of the nanofibers are related to the average particle size D of the ceramic nanoparticles by the following condition: D ≤ (L / d) ≤ 2D, where d is 10~50 in nm, L is 3000~20000 in nm, and D is 150~400 in nm; the thickness of the coating is 0.5~2 μm. The relationship between the mass percentage P% of the ceramic nanoparticles in the coating and the mass percentage K% of the nanofibers in the coating satisfies: 2 < (P / K) 0.7 <25, P is 75~93, K is 1~20; The adhesive is a water-soluble modified polyacrylamide copolymer, specifically a copolymer composed of acrylamide monomers, acrylic monomers, and water-soluble acrylate monomers; wherein the weight ratio of the acrylamide monomers, acrylic monomers, and water-soluble acrylate monomers is 50~80:10~30:10-20; the adhesive accounts for 2~5% of the mass percentage of the coating; The dispersant in the coating has a mass percentage content of 1-3%.
2. The lithium-ion battery separator according to claim 1, characterized in that, 3.8 < (P / K) 0.7 <14.6, P is 83~92, K is 2~12.
3. The lithium-ion battery separator according to claim 1 or 2, characterized in that, The nanofibers are selected from one or more of aramid fibers, cotton fibers, and bacterial cellulose.
4. The lithium-ion battery separator according to claim 1 or 2, characterized in that, The ceramic nanoparticles are selected from one or more of alumina, boehmite, barium titanate, magnesium oxide, silicon oxide, and magnesium hydroxide.
5. The lithium-ion battery separator according to claim 1 or 2, characterized in that, The base membrane is a polyolefin base membrane.
6. The lithium-ion battery separator according to claim 5, characterized in that, The thickness of the base film is 5~25μm; the porosity of the base film is 55~70%.
7. The lithium-ion battery separator according to claim 1 or 2, characterized in that, The dispersant is selected from sodium polyacrylate or ammonium polyacrylate.
8. The method for preparing the lithium-ion battery separator according to any one of claims 1-7, characterized in that, include: Nanofibers, ceramic nanoparticles, binders, dispersants, and solvents are mixed to obtain a slurry; the slurry is then coated onto the base film and dried.
9. The method for preparing a lithium-ion battery separator according to claim 8, characterized in that, The solvent is selected from water.
10. The method for preparing a lithium-ion battery separator according to any one of claims 8 or 9, characterized in that, The drying temperature is 80~100℃, and the time is 4~8h.
11. A lithium-ion battery, characterized in that, The lithium-ion battery separator includes the lithium-ion battery separator according to any one of claims 1-7 or the lithium-ion battery separator prepared by the preparation method according to any one of claims 8-10.
Citation Information
Patent Citations
Lithium ion battery diaphragm and preparation method thereof
CN116581477A
Battery diaphragm, preparation method thereof and battery
CN120527570A